2019
DOI: 10.18502/ijm.v11i3.1327
|View full text |Cite
|
Sign up to set email alerts
|

The antimicrobial effects of zinc oxide-calcium hydroxide mixture fillers: determining the ideal mixture ratio

Abstract: Background and Objectives: Although zinc oxide (ZO)-calcium hydroxide (CaOH) mixtures have been successful regard- ing their absorption rate compatibility with dissolving primary teeth, no study has been conducted on the appropriate mixture ratio to obtain effective antibacterial properties. In this study, we compared antibacterial activity of CaOH-ZO pastes using different mixture ratios sagainst Enterococcus faecalis as an important bacterium in root canal treatment failure. Materials and Methods: Seve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0
8

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 17 publications
0
5
0
8
Order By: Relevance
“…More recently, Meto et al reported a similar C. albicans MIC for copper mixed with CH (125 mg/L) [ 55 ]. Nozari et al reported that they did not observe any antimicrobial effect by zinc oxide on E. faecalis [ 56 ]. Conflicting results have also been reported with the same metals for other oral bacteria, including Streptococcus mutans [ 57 ].…”
Section: Discussionmentioning
confidence: 99%
“…More recently, Meto et al reported a similar C. albicans MIC for copper mixed with CH (125 mg/L) [ 55 ]. Nozari et al reported that they did not observe any antimicrobial effect by zinc oxide on E. faecalis [ 56 ]. Conflicting results have also been reported with the same metals for other oral bacteria, including Streptococcus mutans [ 57 ].…”
Section: Discussionmentioning
confidence: 99%
“…Barium found on ACTIVA TM and SDR™ surfaces is usually associated with the existence of the radiopacifiying filler agent BaO [65]. In terms of Vitrebond TM , the identified zinc has also been reported by other researchers [64], and its bacterial properties have also been studied comprehensively [66]. The large content of lanthanum for Ketac TM Bond can be attributed to its frequent incorporation in the powder constituents of glass-ionomer cements for an opaqueness increase against rays [67] and was also measured by other researchers [68].…”
Section: Discussionmentioning
confidence: 84%
“…21 According to Nozari et al, the combination of CaOH and ZnO, especially when associated with CHX, provides a powerful antimicrobial effect against E. faecalis during root canal treatments. 22 Evans et al discovered that E. faecalis becomes susceptible to the combination of CaOH and chlorhexidine when examining the mechanism of resistance to CaOH in bovine dentin. Because of its method of action, CHX takes just a short time to exert an antibacterial effect on E. faecalis.…”
Section: Discussionmentioning
confidence: 99%